PENGARUH DIGITAL LITERACY DAN TECHNOSTRESS TERHADAP KINERJA ASN DENGAN EMPLOYEE ENGAGEMENT SEBAGAI VARIABEL MEDIASI (STUDI PADA KECAMATAN DI KABUPATEN INDRAGIRI HILIR) - Kasmadi, Kasmadi; Rahmat, Adi; Nasution, Imran Al Ucok (Jurnal Daya Saing, 2026)
This study examines the influence of digital literacy and technostress on the performance of State Civil Apparatus (ASN), with employee engagement as a mediator variable. This quantitative study with a causal design was conducted in four sub-districts in Indragiri Hilir Regency, namely Reteh, Sungai Batang, Enok, and Tanah Merah, involving a total of 104 ASN as respondents. Data collection was carried out through questionnaires, and data analysis adopted a Structural Equation Modeling (SEM) approach based on Partial Least Squares (PLS) with SmartPLS software version 3.2.9. The analysis revealed that digital literacy has a positive and significant influence on employee engagement. However, digital literacy does not have a significant direct influence on ASN performance. On the other hand, technostress was not proven to have a significant influence on either employee engagement or ASN performance. Furthermore, employee engagement does not function as a mediator in the relationship between digital literacy and technostress with ASN performance. These findings indicate that in the context of sub-district-level government, the determining factors of ASN performance tend to be more influenced by structural aspects and the work environment than by psychological variables such as employee engagement or individual competency factors such as digital literacy and technostress.